Investigating VoIP Calls: Law Enforcement Perspective - Chetry, Arjun; Sharma, Uzzal (INFOCOMP Journal of Computer Science, 2025)
Technology is advancing at an unprecedented pace, playing a pivotal role in benefiting society across various domains. However, it also presents formidable challenges for law enforcement agencies. Among the most significant current hurdles, lies in the anonymity criminals can maintain on the internet, particularly through VoIP calls. Policing is an ever-evolving field, demanding investigators to be adaptable in mastering novel investigative techniques. Whether dealing with conventional or tech-related crimes, call detail records have become indispensable components of any investigation. With the surge in smartphone usage and mobile data connections, IP address-based investigations have become imperative, especially when dealing with VoIP calls. Consequently, the ability to trace IP addresses has become a pressing necessity for investigators handling numerous cases involving VoIP calls. This research paper delves into the investigation of VoIP calls, employing IPDR and PCAP files to identify IP addresses.